Do broodstock diets influence viability and larval development of Holothuria mammata? - Venâncio, Eliana (2021)
The intensive exploitation of sea cucumbers, mainly exported to Asian seafood markets, has contributed to deplete natural populations of several species. In Europe, the aquaculture production of these echinoderms is minimal, reflecting the low scientific production on the topic. In Portugal, like in Mediterranean countries, there are native species with high commercial value, which can be potential candidates for aquaculture. The control over the reproductive cycle is an important tool for rearing success, which, in turn, decreases the pressure over natural stocks. However, there are very few studies on the larval development of European species and none on the broodstock maturation in captivity. The present work studied the influence of three diets on the gonadal maturation and larval viability and development of Holothuria mammata. After 120-days of captivity the broodstock groups fed with a mixture of live microalgae (Diet 2) and a mixture of live microalgae and extruded dry food (Diet 3) reached the spawning stage, in contrast to the group fed with a mixture of frozen microalgae (Diet 1). Spawning was induced by thermal shock. Larval rearing from broodstock fed on Diet 2, total mortality was observed on the 12th day, after the onset of mid auricularia stage. The stocks of larvae from the broodstocks fed diets 1 and 3 reached the stage of pentactula on the 27th day. The success in spawning induction and embryonic development suggest that H. mammata may accept different types of diets as frozen microalgae mixes or live microalgae and dry feeds and still produce viable offspring. However, it is essential to develop more studies on the reproductive biology of H. mammata to optimize the hatcheries techniques to broodstock conditioning and larval rearing in captivity.